A dynamic recrystallization based constitutive flow model for micro-machining of Ti-6Al-4V. (May 2022) - Yadav, Rahul; Chakladar, N.D.; Paul, Soumitra
Abstract: The study proposes a coupled thermo-mechanical transient analysis to estimate the cutting performance during micro-machining of Titanium alloy. A constitutive flow model is used along with the effects of dynamic recrystallization which is how the strain-softening evolves at a high strain rate. The frictional stick-slip oscillations that arise from the process are introduced through a Fortran user-subroutine at the chip tool interface. Strain softening and dynamic recrystallization are observed, while the cutting strain exceeds the critical strain of 1.7, owing to strain localization. When the uncut chip thickness reduces from 3 μm to 1 μm which is lesser than the edge radius of the tool, the value of maximum residual stresses increases by a factor of 3.7 and a magnitude of chip reduction coefficient of 2.25 is observed due to a local negative rake angle. The level of residual stress, specific cutting energy and morphology of the chip are validated with literature. In addition, a user-defined material stiffening algorithm is proposed which revealed an increase of compressive residual stress at the surface by 20%. Graphical abstract: Unlabelled Image Highlights: A stick-slip friction algorithm, coupled with a hybrid flow model was proposed for a micro-cutting process. Strain softening and dynamic recrystallization was observed when the cutting strain exceeded a critical strain of 1.7. A nonlinear trend of residual stress was reported when the tool edge radius was comparable to the uncut chip thickness. Thrust force was 21% more than the cutting force at an uncut chip thickness of 1 μm, due to ploughing action.